Barriers to effective project communication: a case Study of Adonai Shipping Chandelling Project for Tullow Ghana Limited - Dowuona-Owoo, Robert (2021)
A Thesis submitted to the Department of Construction Technology and Management, College of Art and Built Environment, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements of the degree of Master of Science in Project Management,